Optimization of Innovation and Entrepreneurship Policy of Scientific and Technological Entrepreneur Talent Using Regional Competitive Advantage Theory - Yu, Xiaoxuan; Du, Baogui (Frontiers in Psychology, 2021)
Under the background of mass entrepreneurship and innovation, innovative entrepreneurship research is urgently needed for entrepreneurs. The aim is to explore the innovative entrepreneurship consciousness of new entrepreneurs. First, the regional competitive advantage theory is discussed. The research method of questionnaire survey is combined with statistical analysis to obtain relevant research data. Quantitative standards are used to measure the impact of regional advantages and policy support on entrepreneurs' innovation and entrepreneurship. The policy content analysis and questionnaire survey are applied to discuss the impact of regional competitive advantage, educational psychology, innovation and entrepreneurship policy, and entrepreneurs' innovation consciousness. Meantime, the policies related to entrepreneurs' innovation and entrepreneurship are further explored. The results show that the proportions of young entrepreneurs suffering anxiety and depression are 29.4% and 27.5%, respectively, which are significantly higher than the national average. Besides, in the test, F = 23.11, P < 0.005, which indicates that all proposed hypotheses are valid. The results suggest that the overall mental health level of young new entrepreneurs is not high, and their consciousness of innovation and entrepreneurship needs to be strengthened. Under the wave of mass innovation and entrepreneurship, the research results can strengthen entrepreneurs’ innovative entrepreneurship consciousness and may have great theoretical and practical significance for improving and optimizing government innovation and entrepreneurship policies.